Algebra 1: Common Core (15th Edition)

Published by Prentice Hall
ISBN 10: 0133281140
ISBN 13: 978-0-13328-114-9

Chapter 1 - Foundations for Algebra - 1-2 Order of Operations and Evaluating Expressions - Practice and Problem-Solving Exercises: 56

Answer

$9+3-(2+4)=6$

Work Step by Step

$9+3-(2+4)=6$ Use PEMDAS (Parentheses, Exponents, Multiplication, Division, Addition, Subtraction) to solve this equation. 1. First, solve the numbers inside the parenthesis. $(2+4)=6$ 2. Next, use addition. $9+3-6=6$ is simplified to $12-6=6$. 3. Now, use subtraction. $12-6=6$, leaving you with $6=6$. By using PEMDAS, we were able to solve the left side of the equation and prove it is equal to the right side.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.